Akkermansia muciniphila Alters Gut Microbiota and Immune System to Improve Cardiovascular Diseases in Murine Model - He, Xin; Bai, Yang; Zhou, Haiyang; Wu, Kemin (Frontiers in Microbiology, 2022)
Gut microbiota plays an important role in a variety of cardiovascular diseases. The probiotics screened based on microbiota can effectively improve metabolism and immune function of the body, which is of great value in the field of cardiovascular disease treatment. Abdominal aortic aneurysms (AAA) refer to the lesion or injury of the abdominal aortic wall resulting in localized bulge, which is one of the cardiovascular diseases with pulsing mass as the main clinical symptom. Previous studies have confirmed that A. muciniphila was depleted in the gut of AAA patients or mice. A. muciniphila is a potential probiotic for the treatment of intestinal microbiome related diseases. Therefore, this study aims to investigate the effects of A. muciniphila on gut microbiota and disease-related biomarkers in AAA mice. C57BL/6J mice were used to construct AAA model and treated with A. muciniphila. Aortic aneurysm formation in AAA group with the increased diameter of the abdominal aorta and inflammatory infiltration. A. muciniphila inhibited the formation of AAA and repaired tissue damage. The number of gut microbiota and α diversity index were decreased in model group. A. muciniphila increased the number of gut microbiota and α diversity in AAA mice. The abundance of uncultured bacterium and Lactobacillus were increased, the abundance of Lachnospiraceae NK4A136 group was reduced in the AAA group. Compared with the control group, the levels of MMP-1, MMP-9, IL-33, CTSB and CTSL in tissue and the levels of IL-6, IFN-γ and CRP in blood were significantly increased, the levels of IL-4, IL-10 and IL-17A in blood were significantly decreased in the AAA group. The intervention of A. muciniphila reversed these changes. Gut microbiota function prediction showed changes in E.coli, Clostridium and Lactobacillus metabolism-related functional pathways. Akkermansia was negatively correlated with Helicobacter and Lactobacillus, and positively correlated with Clostridium_sensu_stricto_1 and Escherichia.Shigella at genus level. In conclusion, A. muciniphila inhibited the formation of AAA by restoring gut microbiota diversity, altering the expression of peripheral immune factors, as well as the functions of E.coli, Clostridium and Lactobacillus, which may provide a new theoretical basis for the application of probiotics in cardiovascular diseases.